A Study of Dialectology on Javanese "Ngoko" in Banyuwangi, Surabaya, Magetan, and Solo - Erlin Kartikasari; Kisyani Laksono; Agusniar Dian Savitri; Diah Yovita Suryarini (Humaniora, 2018)
Dialectology study on Javanese language in Banyuwangi, Surabaya, Magetan and Solo is significant as it reveals the lexical and phonological differences of Javanese “ngoko” in the four areasresearched. The areas were chosen due to the following reason; Banyuwangi is located in the eastern tip of Java Island and directly borders the islands of Bali and Madura, Surabaya is the capital of East Java province as well as a metropolitan city, Magetan is located in the western tip of East Java Province which is directly adjacent to Central Java Province, and Solo is the center of Javanese culture in Central Java. The focus of this research is to calculate the number of lexical and phonological differences of Javanese “ngoko” in Banyuwangi, Surabaya, Magetan and Solo. This research uses quantitative researchwith (the or a) descriptive method. The data of the research is Javanese “ngoko”.The instrument is Nothofer questionnaires modified by Kisyani by developing Swadesh's list into 829 words/phrases. The results of the research reveal(1) the largest number of Javanese “ngoko” lexical is found in Solo while theleast were found in Surabaya. The lexical differences of Javanese “ngoko” in Banyuwangi, Surabaya, Magetan, and Solo resulted in one utterance, two dialects and four subdialects, (2)19 patterns of phonological differences in Javanese “ngoko” were found. Finally, the phonological differences of Javanese “ngoko” in Banyuwangi, Surabaya, Magetan, and Solo resulted in four utterances.